Explaining and tackling undeclared work in South East Europe: Lessons from 2019 Eurobarometer survey - Colin C. Williams (UTMS Journal of Economics, 2021)
The aim of this paper is to evaluate two contrasting ways of explaining and tackling undeclared work. The rational economic actor approach theorizes undeclared work as arising when the benefits of undertaking undeclared work outweigh the costs, and the policy focus is upon deterring undeclared work by increasing the penalties and probability of being caught, whilst the social actor approach theorizes undeclared work as resulting from a lack of vertical trust (in government) and horizontal trust (in others). To evaluate these, evidence from Eurobarometer surveys conducted in 2007, 2013 and 2019 in seven South East European countries is reported. The finding is that although in some time periods there is a significant association between preventing participation in undeclared work and greater perceived penalties and probabilities of detection, there is a strong significant positive association between preventing participation in undeclared work and greater vertical and horizontal trust in all time periods. The theoretical implications are then discussed along with the policy implications.
Keywords: H26; J46; K34; K42; O17; P02; 330; informal sector; shadow economy; tax compliance; tax morale; South East Europe